2016
DOI: 10.1123/jpah.2014-0535
|View full text |Cite
|
Sign up to set email alerts
|

An 8-Week Exercise Intervention Based on Zumba Improves Aerobic Fitness and Psychological Well-Being in Healthy Women

Abstract: These results highlight that Zumba is beneficial to improve fitness and well-being in healthy women, but does not change body composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
40
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 26 publications
2
40
0
5
Order By: Relevance
“…Aerobic exercise that done for 60 minutes can decrease fat folds under the skin and lose body mass [7]. The motivation of many women in doing exercise is to lose body weight, 28 and a good way in order to achieve this objective anecdotally evidence suggests that is Zumba [8]. Zumba exercise can reduce skinfold thickness than aerobic exercise [9].…”
Section: Discussionmentioning
confidence: 99%
“…Aerobic exercise that done for 60 minutes can decrease fat folds under the skin and lose body mass [7]. The motivation of many women in doing exercise is to lose body weight, 28 and a good way in order to achieve this objective anecdotally evidence suggests that is Zumba [8]. Zumba exercise can reduce skinfold thickness than aerobic exercise [9].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous physiological and psychological benefits of Zumba ® have been identified in healthy populations, including improvements in dynamic balance, quality of life, lower pain perception, less interference with daily activities, higher self-perception of physical strength, and greater autonomy and purpose in life. [27][28][29][30] Since many of these aspects are affected in PD, it can be hypothesized that Zumba ® could benefit this population. However, to date there is no study on this type of exercise in neurological populations.…”
Section: Introductionmentioning
confidence: 99%
“…The endurance training consisted of low-and highimpact aerobic dance, which is an effective method to increase physical endurance (Wilmore & Knuttgen, 2003), and the resistance training comprised a progressive weight-lifting programme, which is an effective intervention to improve physical strength (Liu & Latham, 2009). We chose the 8-week period because it had been found that 6 to 8 weeks of either training were enough to both increase aerobic capacity and strength and improve well-being and cardiovascular adaptation to psychological stressor (Delextrat et al, 2016;Spalding et al, 2004). We hypothesised that both endurance-and resistance-trained participants would show lower cardiovascular stress reactivity to and more rapid recovery from psychological stressor, and less life stress, as a consequence of the training.…”
mentioning
confidence: 99%